MODEL ALTERNATIF UNTUK MEMBANGUN SISTEM INFORMASI PERENCANAAN PAJAK DAERAH DAN RETRIBUSI DAERAH - Aji, Tony Seno (Universitas Muhammdaiyah Surakarta, 2010)
This research aimed to develop and coincidentally to improve the planning model of current the regional revenue and retribution (PDRD). This research is also to accommodate PDRD, the managerial capability of government and the regional macroeconomic condition, which have been neglected. Macroeconomic variable selection that influenced PDRD for the two-wheel and four-wheel vehicles were the government expenditure and the interest rate, and for more-than-four-wheel vehicles were the government expenditure and exchange rate. The potential of parking tax which was achieved from the tax payers in the year 2009 reached by Rp733,937,632 and the total value of parking retribution potential in that same year was Rp548,440,103. The attainment of PDRD only around half from its potency. The trend of Financial Capability Index from 2004 to 2008 declined and belonged to medium category. As a whole, the coverage ratio of the regional revenue and retribution of Gresik Municipality was 48.58 percent, which means that the collectiveness of the regional revenue and retribution is considered to be in the condition of far below its optimum level.